Spatiotemporal Dynamics of Oligofructan Metabolism and Suggested Functions in Developing Cereal Grains - Peukert, Manuela; Thiel, Johannes; Mock, Hans-Peter; Marko, Doris; Weschke, Winfriede; Matros, Andrea (Frontiers in Plant Science, 2016)
Oligofructans represent one of the most important groups of sucrose-derived water–soluble carbohydrates in the plant kingdom. In cereals, oligofructans accumulate in above ground parts of the plants (stems, leaves, seeds) and their biosynthesis leads to the formation of both types of glycosidic linkages (ß(2,1); ß(2,6)-fructans) or mixed patterns. In recent studies, tissue- and development- specific distribution patterns of the various oligofructan types in cereal grains have been shown, which are possibly related to the different phases of grain development, such as cellular differentiation of grain tissues and storage product accumulation. Here, we summarize the current knowledge about oligofructan biosynthesis and accumulation kinetics in cereal grains. We focus on the spatiotemporal dynamics and regulation of oligofructan biosynthesis and accumulation in developing barley grains (deduced from a combination of metabolite, transcript and proteome analyses). Finally, putative physiological functions of oligofructans in developing grains are discussed.